2022
DOI: 10.3390/v14020356
|View full text |Cite
|
Sign up to set email alerts
|

Metagenome-Assembled Viral Genomes Analysis Reveals Diversity and Infectivity of the RNA Virome of Gerbillinae Species

Abstract: Rodents are a known reservoir for extensive zoonotic viruses, and also possess a propensity to roost in human habitation. Therefore, it is necessary to identify and catalogue the potentially emerging zoonotic viruses that are carried by rodents. Here, viral metagenomic sequencing was used for zoonotic virus detection and virome characterization on 32 Great gerbils of Rhombomys opimus, Meriones meridianus, and Meiiones Unguiculataus species in Xinjiang, Northwest China. In total, 1848 viral genomes that are pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…A total of 28 new PBV strains were obtained from fecal samples of wild Rattus norvegicus , indicating that Rattus norvegicus is one of the critical wildlife reservoirs for PBV. Two studies on the diversity of RNA viruses in wild animals in the plateau region of western China showed that a large number of segmented PBVs and a small number of unsegmented PBVs were found in the feces of Tibetan rats and Himalayan zoko rats, which were generally consistent with PBVs in woodchuck [ 49 , 50 ]. Most PBVs in this experiment were grouped with known genotypes but clustered with other animals.…”
Section: Discussionmentioning
confidence: 95%
“…A total of 28 new PBV strains were obtained from fecal samples of wild Rattus norvegicus , indicating that Rattus norvegicus is one of the critical wildlife reservoirs for PBV. Two studies on the diversity of RNA viruses in wild animals in the plateau region of western China showed that a large number of segmented PBVs and a small number of unsegmented PBVs were found in the feces of Tibetan rats and Himalayan zoko rats, which were generally consistent with PBVs in woodchuck [ 49 , 50 ]. Most PBVs in this experiment were grouped with known genotypes but clustered with other animals.…”
Section: Discussionmentioning
confidence: 95%
“…Our work on viral diversity differs from previous investigations due to distinct study approaches [ 4 , 37 ]. While metagenomics and metatranscriptomics have previously characterized rodent virome at organ level, much remains to be understood regarding the diversity of zoonotic viruses at species and habitat levels [ 35 , 38 ]. This knowledge gap underscores the complexity of host-virus interactions in Yunnan rodent populations, with unique viral profiles across species and organs, with spleen samples consistently exhibiting high mammal viral diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Putative virus contigs were compared with the NT database by using BLAST, and the result of the best hit with e ≤ 10 −5 was selected for species annotation. 39 The viruses were annotated with contig percentages at the family and species levels. The reads per kilobase per million mapped reads (RPKM) for each virus contig were calculated.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Putative virus sequences with a similarity of <80% were searched in the virus NT and NR databases by using BLASTN (version 2.9.0+; ) and BLASTX (version 2.9.0+; ). Putative virus contigs were compared with the NT database by using BLAST, and the result of the best hit with e ≤ 10 –5 was selected for species annotation . The viruses were annotated with contig percentages at the family and species levels.…”
Section: Materials and Methodsmentioning
confidence: 99%